Functional adaptation of the masticatory system to implant-supported mandibular overdentures - Giannakopoulos, Nikolaos Nikitas; Corteville, Frédéric; Kappel, Stefanie; Rammelsberg, Peter; Schindler, Hans J.; Eberhard, Lydia (Clinical oral implants research, 2017)
Objectives The purpose of this study was to investigate the adaptation behavior of the stomatognathic system after immediate loading (24 to 72 h after surgery) of two implants supporting mandibular overdentures, assessed on insertion and three months later. The study hypothesis was that insertion of the overdentures would significantly change masticatory performance and muscle activity at both times. Material and methods Thirty subjects (nine female, mean age 69.64 ± 11.81 years; 21 male, mean age 68.67 ± 7.41 years) who participated in a randomized clinical trial were included in the study. Each patient was examined three times: (i) at baseline, after already having worn new dentures for three months (T1); (ii) immediately after insertion of the overdentures on the implants (T2); and (iii) after an adaptation period of three months (T3). Examination comprised assessment of masticatory performance with artificial test food (Optocal), and simultaneous bilateral surface EMG recording of the masseter and anterior temporalis muscles. Particle-size distribution (representative value X50), maximum muscle contraction (MVC), and total muscle work (TMW; area under the curve) were compared by use of repeated-measures analysis of variance (ANOVA). Results At T3, all measured variables (i.e., masticatory performance and muscle activity) were significantly different from those at T1. At T2, no significant changes were observed. The study hypothesis had to be rejected for T2 but accepted for T3. Conclusion Functional rehabilitation (in terms of masticatory performance and masticatory muscle activity) does not occur immediately after immediate loading of two implants with mandibular overdentures, but requires a significant time for functional improvement.